La creazione d’impresa di origine accademica. Uno studio sull’intenzione imprenditoriale - Thomas, Antonio; Passaro, Renato; Scandurra, Giuseppe (Piccola Impresa / Small Business, 2014)
<!--[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]--> To be able to support and spread a virtuous entrepreneurship is almost unanimously considered a possible solution to the problems caused by the economic and financial crisis in many Western countries. In order to generate virtuous entrepreneurship, that is high-tech and cutting-edge initiatives with high prospects for future expansion, the university system is able to play a relevant role through the academic entrepreneurship. In this perspective, the contribution specifically examines an aspect of this academic entrepreneurship proposing an analysis of the entrepreneurial intent expressed by a sample of university students. To this purpose we adopt an application of the well-known Theory of planned behavior. The findings obtained confirm the effectiveness of this Theory to predict people’s entrepreneurial choice. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->